Políticas industriais: definições, fundamentações teóricas e avaliações - Strachman, Eduardo [UNESP]; Avellar, Ana Paula (My University, 2014)
The purpose of this paper is to essentially provide a theoretical framework to industrial policies, especially showing the reasons for preference of a theoretical framework that is not based on equilibrium, and not based on maximization. We sought to define these policies, highlighting their positive results – at least potentially – in terms of some parameters (production, efficiency, productivity, income, welfare etc.). In this sense, we defined industrial policy, also analyzing the reasons for the usual lack of concern with a more rigorous theoretical framework for industrial policies. Following that, we briefly discussed whether or not a certain theory can lay the foundation for these policies, also examining if such theories are important (or not) in empirical terms. In the fourth section, we investigated the possible use of industrial policies, emphasizing market failures, public goods, non-competitive markets, externalities and technological development. Finally, we discussed about evaluation approaches of industrial and technological policies, focusing with more detail on the challenges related to the evaluation of economic effects of industrial and technological policies, and the methodologies of evaluation of these policies.

O objetivo deste artigo é, essencialmente, fundamentar teoricamente as políticas industriais, sobretudo mostrando as razões da preferência por um referencial teórico não equilibrista e não maximizador. Buscamos definir estas políticas, destacando seus resultados positivos – pelo menos potencialmente – em termos de alguns parâmetros (produção, eficiência, produtividade, renda, bem-estar, etc.). Para isso, definimos política industrial, analisando também as razões da frequente despreocupação com uma fundamentação mais rigorosa das políticas industriais. Em seguida, apresentamos sucintamente uma teoria capaz de embasar essas políticas, ao mesmo tempo em que examinamos se tais teorias são importantes (ou não), em termos empíricos. No quarto item, investigamos a possível utilidade da política industrial, enfatizando falhas de mercado, bens públicos, mercados não competitivos, externalidades e desenvolvimento tecnológico. Por fim, discutimos sobre as formas de avaliação das políticas industriais e tecnológicas, atentando mais detalhadamente para os desafios na avaliação dos efeitos econô- micos de políticas industriais e tecnológicas e para as metodologias de avaliação destas políticas.
Keywords: Desenvolvimento; Economia Evolucionista; Economia industrial; Instituições; Política industrial; Política Científica e Tecnológica